Exploring Mathematics Anxiety among Undergraduate Engineering Students - Paudel, Krishna Chandra (Journal of Science and Technology, 2024)
This paper explores the level of mathematics anxiety and the factors influencing the undergraduate study of engineering mathematics. Semi-structured interviews were conducted on purposively selected ten bachelor-level engineering students. The data thus obtained were analyzed using descriptive qualitative research design. Four main themes were identified viz. (1) students' low self-esteem, (2) unfriendly pedagogical practices, (3) unfavorable institutional decisions and practices, and (4) a hostile examination system and laden contents. This study recommends a support system that includes counselling, motivation, teacher support, etc. to overcome mathematics anxiety among bachelor level engineering students.